Analysis and performance exploration of high performance (HfO2) SOI FinFETs over the conventional (Si3N4) SOI FinFET towards analog/RF design. (December 2018) - Jain, Neeraj; Raj, Balwinder
Abstract: Nowadays FinFET devices have replaced the MOS devices almost in all complex integrated circuits of electronic gadgets like computer peripherals, tablets, and smartphones in portable electronics. The scaling of FinFET is ongoing and the analog/RF performance is most affected by increased SCEs (short channel effects) in sub 22 nm technology nodes. This paper explores the analog/RF performance study and analysis of high performance device-D2 (conventional HfO2 spacer SOI FinFET) and device-D3 (source/drain extended HfO2 spacer SOI FinFET) over the device-D1 (conventional Si3 N4 spacer SOI FinFET) at 20 nm technology node through the 3-D (dimensional) simulation process. The major performance parameters like I on (ON current), I off (OFF current), g m (transconductance), g d (output conductance), A V (intrinsic gain), SS (sub-threshold slope), TGF = g m / I d (trans-conductance generation factor), V EA (early voltage), GTFP (gain trans-conductance frequency product), TFP (tans-conductance frequency product), GFP (gain frequency product), and f T (cut-off frequency) are studied for evaluating the analog/RF performance of different flavored SOI FinFET structures. For analog performance evaluation, device-D3 and D2 give better results in terms of g m, I D (drain current) and SS parameters, and for RF performance evaluation device-D1 is better in terms of f T, GTFP, TFP, and GFP parameters both at low and high values of V DS = 0.05 V and V DS = 0.7 V respectively.